2022
DOI: 10.32598/bcn.2021.973.3
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Human Umbilical Cord-Derived Mesenchymal Stem Cells in Dopaminergic Neurons in a Three-Dimensional Culture

Abstract: Introduction: The induction of from human umbilical cord-derived mesenchymal stem cells (HUC-MSCs) toward dopaminergic neurons is a major challenge in tissue engineering and experimental and clinical treatments of various neurodegenerative diseases including Parkinson’s disease. This study aimed to differentiate HUC-MSCs into dopaminergic neuron-like cells. Methods: After HUC-MSCs isolation and characterizations, they transferred onto matrigel- coated plates and incubated with a cocktail of dopaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…12,13 MSCs have the capacity for multidirectional differentiation and self-renewal, and they can differentiate into end-stage cells such as lipogenic cells, chondrogenic cells, and neuronal cells in vitro when subjected to various stimulating factors and induction media. [14][15][16] These qualities have caused MSCs to gradually gain attention in the fields of medicine and tissue engineering in recent decades, and numerous experiments have now demonstrated that MSCs are a very promising research area and have extensive research significance for the regeneration of various tissues and cells, such as bone, skin, and nerves. 7,17,18 The emergence and growth of MSCs have greatly aided the search for novel treatments for several disorders.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 MSCs have the capacity for multidirectional differentiation and self-renewal, and they can differentiate into end-stage cells such as lipogenic cells, chondrogenic cells, and neuronal cells in vitro when subjected to various stimulating factors and induction media. [14][15][16] These qualities have caused MSCs to gradually gain attention in the fields of medicine and tissue engineering in recent decades, and numerous experiments have now demonstrated that MSCs are a very promising research area and have extensive research significance for the regeneration of various tissues and cells, such as bone, skin, and nerves. 7,17,18 The emergence and growth of MSCs have greatly aided the search for novel treatments for several disorders.…”
Section: Introductionmentioning
confidence: 99%